2018
DOI: 10.3892/ol.2018.8979
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of resibufogenin on gastric carcinoma cells through the phosphoinositide 3‑kinase/protein kinase�B/glycogen synthase kinase 3β signaling pathway

Abstract: The aim of the present study was to investigate the anticancer effect of resibufogenin in gastric carcinoma cells through the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/glycogen synthase kinase 3β (GSK3β) signaling pathway. MGC-803 cells were treated with 0, 1, 2, 4 and 8 µM resibufogenin for 12, 24 and 48 h. Cell viability and apoptosis were measured using an MTT assay and annexin V staining. Caspase-3 and caspase-8 activity were identified using caspase-3 and caspase-8 activity kits and a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…RB has recently been identified as a potential anticancer agent for cancer treatment (Han et al, 2018; Li, Jiang, et al, 2019; Lu et al, 2018). For example, RB inhibited the development of ovarian cancer (Li, Jiang, et al, 2019), gastric cancer (Lu et al, 2018), and CRC (Han et al, 2018). In this study, we found that RB inhibited CRC cell proliferation and promoted cell death in a time‐ and dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RB has recently been identified as a potential anticancer agent for cancer treatment (Han et al, 2018; Li, Jiang, et al, 2019; Lu et al, 2018). For example, RB inhibited the development of ovarian cancer (Li, Jiang, et al, 2019), gastric cancer (Lu et al, 2018), and CRC (Han et al, 2018). In this study, we found that RB inhibited CRC cell proliferation and promoted cell death in a time‐ and dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is an urgent need to find new drugs for CRC treatment. RB has recently been identified as a potential anticancer agent for cancer treatment (Han et al, 2018;Li, Jiang, et al, 2019;Lu et al, 2018). For example, RB inhibited the development of ovarian cancer (Li, Jiang, et al, 2019), gastric cancer (Lu et al, 2018), and CRC (Han et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, RB has been demonstrated to suppress colorectal cancer cell proliferation and metastasis by promoting necroptosis (Han et al, 2018). In gastric cancer, RB has been shown to inhibit cell proliferation and induce apoptosis by activating the PI3K/AKT/GSK3β signaling pathway (Lu et al, 2018). Consistent with previous studies, our results demonstrated that RB was able to inhibit cell proliferation and invasion in a dose‐dependent manner in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Protein concentrations were determined by DC protein assay reagent (Bio-Rad) and extracts resolved by SDS/PAGE, then transferred to PVDF membranes (Bio-Rad). Membranes were blocked for 2 h at room temperature in 0.1% TBS-Tween-20 containing 5% non-fat dried milk, washed, and then incubated with the following specific primary antibodies; anti-phospho-Akt (Ser473, #4060 from Cell Signaling Technology, 1:1000 dilution) (Lu et al, 2018), anti-total-Akt (#9272, 1:1000 dilution) (Li et al, 2018), anti-phospho-IGF-I Receptor-β (Tyr1135/1136)/Insulin Receptor-β (Tyr1150/1151) (#3024, 1:500 dilution) (De Filippis et al, 2018), anti-total-IGF1Rβ (sc-713# from Santa Cruz Biotechnology Inc., Dallas, Texas, 1:200 dilution) (Pagesy et al, 2016), anti-phospho-p44/42 ERK1/2 (Thr202/Tyr204, #9101, 1:2000 dilution) (Go et al, 2018), anti-total ERK1/2 (#4695, 1:3000 dilution) (Meng et al, 2018); Anti-Actin (sc-1616 from Santa Cruz Biotechnology, 1:1000 dilution) (Perić et al, 2017); and anti-CgA (HPA017369, Sigma-Aldrich, 1:500 dilution) (Marbiah et al, 2014). After washing, membranes were incubated with HRP-conjugated secondary antibodies (Santa Cruz Biotechnology) and proteins visualized using a Super Signal Chemiluminescence Assay kit (Pierce, Grand Island, NY).…”
Section: Methodsmentioning
confidence: 99%